The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1254/jjp.29.587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorpromazine on Lipolysis in Brown and White Adipose Tissues of Cold-Exposed Rats

Abstract: Abstract-Effectsof chlorpromazine (CPZ) on lipolysis in brown (interscapular: IBAT) and white (epididymal: EWAT) adipose tissues in cold-exposed rats were studied in vitro. Adult male Wistar-Imamichi rats were exposed to 4°C for 1 (acute cold-exposed) or 30 (cold-acclimated) days. The spontaneous free fatty acid (FFA) release from interscapular brown adipose tissue (IBAT) of control rats, was three fold higher than epididymal white adipose tissue (EWAT). FFA release from the EWAT of acute cold-exposed rats was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This increase in BAT DA content lasts for at least 30 days, if rats are maintained at a low temperature; thus, while in a first period cold induces opposite effects on BAT DA and NE, after 30 days BAT content of both amines is increased. No significant increase in BAT DA in adult rats was found following 24 hours exposure to 4'C (Uchida 1979).…”
Section: Discussionmentioning
confidence: 69%
“…This increase in BAT DA content lasts for at least 30 days, if rats are maintained at a low temperature; thus, while in a first period cold induces opposite effects on BAT DA and NE, after 30 days BAT content of both amines is increased. No significant increase in BAT DA in adult rats was found following 24 hours exposure to 4'C (Uchida 1979).…”
Section: Discussionmentioning
confidence: 69%
“…Since the effect of dopamine was similar to that of forskolin, a stimulator of adenylate cyclase, Maxwell et al (22) have suggested the presence of D1 receptors on brown adipocytes. Evidence for a dopaminergic role in BAT physiology is further supported by the detection of dopamine in BAT (23)(24)(25) (27) but also dopamine receptors are involved in regulation of BAT. In adult humans, significant levels of dopamine have been detected in plasma (28), and in newborn human subjects the urine level of dopamine is twice the level of norepinephrine (29). The origin of the plasma dopamine (28) and the source of dopamine that may be involved in regulation of BAT are poorly understood.…”
mentioning
confidence: 95%